An Analysis of Broken Plural Forms in the Novel, Al-Sukkarivyah, by Najuib Mahfouz - Goodarzi, Fatemeh Lotfi (2009)
This research is a d escriptive study of the broken plural in the al-Sukariyah novel of novelist Najib Mahfouz. Broken plural is one of the important inflections in the Arabic language. It is the third type of plural in Arabic. The first plural type is the sound masculine plural while the second one is the sound feminine plural . Broken plural is described a s the language strange phenomenon a s it has a lot of measures. This study tries to search for the development in the broken plural formulas. These formulas are discussed in chapter three with reference to the novel at hand. Specifying all the formulas of the broken plural either descriptive or morphological, and finding the fundamental grammatical rules that govern the broken plural. This research discusses two important parts; the first of which is the theoretical part in which types of plurals are discussed for the sake of making this study comprehensible, while the second part deals with the practical side in which broken plurals are figured out from the novel. All the broken plural forms are explained and analyzed thoroughly with reference to definitions and explanations of old gram marians. The expected results out of this study would be that the research explores the structure of the broken plural in the novel that goes in line with the theories of old grammarians and also the structures that oppose those theories.